DEVELOPMENT OF DEEPWATER FACIES AND PALEOGEOGRAPHY MODEL IN FORE ARC BASIN: AN EXAMPLE FROM THE HALANG FORMATION, BANYUMAS SUB BASIN, CENTRAL JAVA - Ardenta, Henrycus Nesha (DEPARTEMEN TEKNIK GEOLOGI FT UGM, 2016)
Mio-Pliocene Halang Formation is mostly distributed along Southern Serayu Mountains, Central Java. This formation is commonly deposited on deep marine environment and interpreted as a product of submarine fan deposits. This paper is concerned to interpret facies development and paleogeography model of Halang Formation during Middle Miocene in Cibangkong Area, Banyumas Sub Basin. This study is also passed several methods based on outcrop observations and laboratory analysis. The primer data such as measuring section, biostratigraphic and granulometry analysis, supported to build facies development. Integrated facies model, paleocurrent measurement, and secondary data (gravity, provenance, structure trend, and basement configuration) build a paleogeography model. In study area, Halang Formation is particularly characterized by interbeded carbonaceous sandstones facies and carbonaceous claystone facies which is capped by massive sandstone facies with erosional contact. The integrated analysis could lead interpretation in the study area that Halang Formation is a part of the fan lobes facies. Paleogeography model shows that sediment supply comes from Southwest to the Northeast. Karangbolong high is located in the West to Southwest, is thought to be the center erosion and supplies the Halang Formation. Discovery of volcanic and limestone fragment in one of sandstone layer in Halang Formation supported the paleogeography model. The presence of volcanic and carbonate material simultaneously indicates that there is a volcanic activity in proto-Kumbang as well as the possibility of carbonate that have grown in Karangbolong High in West to Southwest of the research areas. Kata kunci : Halang Formation, Deepwater Facies, Paleogeography